Winning businesses in product development the critical success factors - Cooper, Robert G.
Robert G. Cooper and Elko J. Kleinschmidt uncover the key drivers of new product performance at the business unit level.
A formal new product process isn't enough-you need a high-quality process, a clear and visible strategy, enough people and money, and a respectable R&D budget. How does your program rate on these 10 metrics?
This benchmarking study of 161 business units uncovered the key drivers of new product performance at the business unit level. Ten different performance measures were gauged, including percentage of sales by new products, profitability and success rate. The ten gauges were reduced to two key performance dimensions-profitability and impact-which defined the "performance map." Nine possible drivers-including strategy, process, organizational design, and climate for innovation-were investigated, and four key drivers of performance were identified; namely, a high-quality new product process, the new product strategy for the business unit, resource availability, and R&D spending levels. Merely having a formal new product process had no impact.
Keywords: Product development